Bilateral morphological variation of abductor pollicis longus and extensor pollicis brevis tendons: a cadaveric case report with clinical perspective - Srinivasa RS,; Varna Taranikanti,; Mohammed AM, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Concurrent morphological variations of abductor pollicis longus (APL) and extensor pollicis brevis (EPB) are seldom reported in literature. Extra slips of APL and EPB are clinically significant as they are used to reconstruct the ruptured tendons in the hand. Herein, we report bilateral morphological variations of APB and EPB in a male cadaver. On each side of forearm, APL was divided into two tendinous slips within the first compartment of extensor retinaculum. One of these slips inserted on to the radial side of base of first metacarpal bone close to the insertion of EPB, and the other slip inserted on to both abductor pollicis brevis and opponens pollicis. EPB divided into two tendons slips deep to the extensor retinaculum. These slips were found to be inserted on to the dorsal surface of the base of proximal phalanx while the other inserted on to the radial aspect of the base of first metacarpal bone, close to the insertion of APL tendon. These additional slips are frequently associated with first carpo-metacarpal subluxation and de Quervain’s syndrome and may be responsible for the clinical manifestations of these diseases. In addition, knowledge of the morphological variations of APL and EPB can aid orthopaedic and plastic surgeons in performing successful tendon transplants.